2012
DOI: 10.1017/s0007485312000247
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype variations in Italian populations of the peach-potato aphid Myzus persicae (Hemiptera: Aphididae)

Abstract: In this study, we present cytogenetic data regarding 66 Myzus persicae strains collected in different regions of Italy. Together with the most common 2n = 12 karyotype, the results showed different chromosomal rearrangements: 2n = 12 with A1-3 reciprocal translocation, 2n = 13 with A1-3 reciprocal translocation and A3 fission, 2n = 13 with A3 fission, 2n = 13 with A4 fission, 2n = 14 with X and A3 fissions. A 2n = 12-13 chromosomal mosaicism has also been observed. Chromosomal aberrations (and in particular al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The chromosome number and karyotype structure of aphids have been studied in a large number of species over the past few decades showing that chromosomal variations are relatively common within some species [Blackman, 1980;Manicardi et al, 2002Manicardi et al, , 2015aMonti et al, 2011Monti et al, , 2012aRivi et al, 2012Rivi et al, , 2013Mandrioli et al, 2014a]. This is not surprising since aphids have holocentric chromosomes with kinetic activity spread along the whole chromosome axis [Blackman, 1980].…”
Section: © 2016 S Karger Ag Baselmentioning
confidence: 99%
See 2 more Smart Citations
“…The chromosome number and karyotype structure of aphids have been studied in a large number of species over the past few decades showing that chromosomal variations are relatively common within some species [Blackman, 1980;Manicardi et al, 2002Manicardi et al, , 2015aMonti et al, 2011Monti et al, , 2012aRivi et al, 2012Rivi et al, , 2013Mandrioli et al, 2014a]. This is not surprising since aphids have holocentric chromosomes with kinetic activity spread along the whole chromosome axis [Blackman, 1980].…”
Section: © 2016 S Karger Ag Baselmentioning
confidence: 99%
“…The peach potato aphid Myzus persicae (Sulzer) is one of the most extensively studied aphid species in the world in terms of lifecycle, migration, population genetics, and cytogenetics, and several molecular and cytogenetic analyses have been performed in order to elucidate the structure of its genome and karyotype [Blackman, 1980;Manicardi et al, 2002Manicardi et al, , 2015aMonti et al, 2011Monti et al, , 2012aRivi et al, 2012Rivi et al, , 2013.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This view is vindicated by Ramsey et al 28 who identified 2423 novel genes specific to M. persicae from a large collection of aphids from different geographical regions and found high polymorphism in nucleotide sequence tags. The present and some previous studies from Tripura 2,5,8,19,26,27 bring out that discrimination in host plant utilization in asexual lineages of M. persicae and other aphid species appears to be a common phenomenon and, therefore, requires a focussed approach in understanding aphid-food plant relationship and management of aphid populations on specific host plants 2,4,7,22 .…”
mentioning
confidence: 74%
“…Distinct phenotypes and genotypes of M. persicae have been recorded from different parts of the world under diverse conditions and from different host plants, both wild and cultivated 5,17,23,25,26 . The recorded differences in phenotypes, based on differences in genotypes, are from the secondary host plants of diverse plant families which vary from region to region 27,28 . Apterous viviparous female morph of aphids, which is the colonizer of food plants, appears to undergo constant changes in its structures and functions in order to adapt to variable conditions of host environments including presence of allelochemicals which profoundly influence the selection process of host plant 28,29 .…”
mentioning
confidence: 99%